2007
DOI: 10.1038/sj.bjc.6603539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cancer chemopreventive efficacy of rice bran in genetic mouse models of breast, prostate and intestinal carcinogenesis

Abstract: Brown rice is a staple dietary constituent in Asia, whereas rice consumed in the Western world is generally white, obtained from brown rice by removal of the bran. We tested the hypothesis that rice bran interferes with development of tumours in TAg, TRansgenic Adenocarcinoma of the Mouse Prostate (TRAMP) or Apc Min mice, genetic models of mammary, prostate and intestinal carcinogenesis, respectively. Mice received rice bran (30%) in AIN-93G diet throughout their post-weaning lifespan. In TAg and TRAMP mice, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 33 publications
1
43
1
1
Order By: Relevance
“…Some of these phenolic compounds have been reported to inhibit the growth of human breast and colon cancer cells [85]. There is no evidence to indicate that rice husk is carcinogenic or mutagenic.…”
Section: Anti-cancer Effect Of Rice By-productsmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of these phenolic compounds have been reported to inhibit the growth of human breast and colon cancer cells [85]. There is no evidence to indicate that rice husk is carcinogenic or mutagenic.…”
Section: Anti-cancer Effect Of Rice By-productsmentioning
confidence: 96%
“…Rice bran inhibits the growth of human colon cancer cells [85], and rice bran consumption reduces the number of intestinal adenomas in APC Min mice, an animal model of human familial adenomatous polyposis (FAP) [86]. Finally, DMH-and AOM-induced preneoplastic lesions are inhibited by rice bran-derived sphingolipids in the colons of rats [87,88].…”
Section: Anti-cancer Effect Of Rice By-productsmentioning
confidence: 99%
“…To our knowledge, few studies have examined the effect of rice on colorectal carcinogenesis, although several have found that individual components of rice are protective. For example, it was found that water-soluble rice bran hemicellulose prevents 1,2-dimethylhydrazine (DMH)-induced colonic tumors in rats (Aoe et al, 1993); rice germ prevents azoxymethane (AOM)-induced colonic aberrant crypt foci (ACF, a preneoplastic lesion of colon cancer) and tumors in rats (Kawabata et al, 1999); extracts of brown rice and rice bran inhibit the growth of human colon cancer cells (Hudson et al, 2000); consumption of rice bran reduces the number of intestinal adenomas in APC Min mice, an animal model of human familial adenomatous polyposis (FAP) (Verschoyle et al, 2007); and rice bran-derived sphingolipids inhibit DMH-and AOM-induced preneoplastic lesions in the colon of rats (Inamine et al, 2005;Sunagawa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Rice (Oryza sativa) is a staple food of over half the world's population especially in Asia, where the incidence of colorectal cancer is markedly lower than that in the Western world (Hudson, Dinh, Kokubun, Simmonds, & Gescher, 2000;Verschoyle et al, 2007). Since the consumption of rice is a major dietary difference between Asian and Western countries, it is important to determine whether rice can affect colorectal cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Serat kedelai mengandung pektin, galaktomanan, dan arabinogalaktan yang memiliki viskositas yang tinggi. Komponen serat ini dapat memperlambat laju pencernaan dan penyerapan glukosa (Verschoyle et al, 2007). Pengaruh dari serat kedelai menjadi penyebab penurunan laju pencernaan yang berakibat pada perlambatan penyerapan glukosa dengan membatasi laju difusi intraluminal glukosa dengan penyerapan permukaan.…”
Section: Kadar Gula Darah Puasa (Gdp)unclassified